2022
DOI: 10.3390/antiox11071317
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidative Role of Hygrophila erecta (Brum. F.) Hochr. on UV-Induced Photoaging of Dermal Fibroblasts and Melanoma Cells

Abstract: Antioxidants are an important strategy for treating photoaging because excessive reactive oxygen species (ROS) are produced during UV irradiation. The therapeutic effects of methanol extracts of Hygrophila erecta (Brum. F.) Hochr. (MEH) against UV-induced photoaging were examined by monitoring the changes in the antioxidant defense system, apoptosis, extracellular matrix (ECM) modulation, inflammatory response, and melanin synthesis in normal human dermal fibroblast (NHDF) cells and melanoma B16F1 cells. Four … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 62 publications
1
3
0
Order By: Relevance
“…A previous study verified that UVB exposure could destroy the equilibrium between oxidative and antioxidant defense systems in skin through generating excessive ROS, including H 2 O 2 , • OH, and O 2 •– , which could reduce the activities of antioxidant enzymes and induce an oxidative stress response. Consistent with this finding, our research showed that topical administration of Rk1 significantly inhibited ROS overproduction during UV irradiation of BALB/c nude mouse skin and HaCaT keratinocytes. Additionally, antioxidant enzymes ( e.g.…”
Section: Discussionsupporting
confidence: 87%
“…A previous study verified that UVB exposure could destroy the equilibrium between oxidative and antioxidant defense systems in skin through generating excessive ROS, including H 2 O 2 , • OH, and O 2 •– , which could reduce the activities of antioxidant enzymes and induce an oxidative stress response. Consistent with this finding, our research showed that topical administration of Rk1 significantly inhibited ROS overproduction during UV irradiation of BALB/c nude mouse skin and HaCaT keratinocytes. Additionally, antioxidant enzymes ( e.g.…”
Section: Discussionsupporting
confidence: 87%
“…Sunburn cells, representative keratinocytes undergoing apoptosis post UV exposure, are seen as a protective measure, eliminating potentially malignantly transformed cells [52]. Such a mechanism has been detailed in a plethora of studies, particularly emphasizing UV radiation's apoptotic impacts, evaluated primarily through the Annexin V-FITC/PI method via flow cytometry [59][60][61][62][63][64].…”
Section: Discussionmentioning
confidence: 99%
“…12. Intracellular Melanin Production and Tyrosinase Activity Assay B16F10 cells were incubated with or without kanuka leaf extract in the presence of 100 nM α-MSH for 24 h, and 100 μg/mL arbutin was applied as the positive control [14,15]. The medium was incubated for 48 h, and the absorbance was measured on a microplate reader detected at 475 nm [16].…”
Section: Western Blotting Assaymentioning
confidence: 99%